Use of process simulator to enhance the teaching‐learning process of flow of fluids for engineering students. Issue 4 (25th April 2018) - de Lucas‐Consuegra, Antonio; Serrano, Angel; Llanos, Javier
Abstract: This manuscript shows how a commercial process simulation software such as Aspen–Hysys can be implemented to enhance the learning experience of Chemical Engineering students in Fluid Mechanics. To this end, a 15 hr practical computer lab is taught as a complement to the Fluid Mechanics lecturer classes at the end of the semester which allow to summarize in a practical way the main concepts of internal flow of fluids. We revisited here five representative learning working cases of this practical lab which includes: pressure drops calculation in pipes and conduction accidents, study of the variation of fluid properties profiles along a piping network, liquid and gases pumping energy calculation, and the study of cavitation phenomenon by the calculation of the Net Positive Suction Head (NPSH) in pumps. The proposed practical cases are also solved with the mass and energy balances equations studied in the lecturer classes to verify the obtained results which additionally are discussed according to a number of questions proposed on each practical example. The students feedback and satisfaction survey shows an overall score of the Fluid Mechanics practical course by the students of 8.2 out of 10 showing that this computer lab improves the efficiency of the Fluid Mechanics course since it let students to better understand the behavior of fluids in motion and the basic methods for the analysis and preliminary calculations of a wide variety of problems encountered in internal flow of fluids.